Domestic Credit and the Balance of Payment Deficit: Evidence from a Heterogeneous Panel of Five Selected Mena Countries - Ghilous Azeddine (Sciendo, 2021)
This study investigated the relationship between domestic credit and net foreign assets in the long run through the monetary approach to the balance of payments (MABP) for a panel of five selected MENA countries (Jordan, Egypt, Algeria, Morocco, Tunisia) during the period extending from 1980 to 2019. It employed the second-generation methods in panel data analysis to deal with cross-sectional dependence (CSD) and slope heterogeneity. According to the panel results for Common Correlated Effects Mean Group (CCEMG) and Augmented Mean Group (AMG) estimators, domestic credit has a significant negative impact on net foreign assets in the long run. The country-specific results for the AMG estimator strongly supported the MABP propositions in Jordan, Morocco, and to a lesser extent, in Egypt and Algeria. As for Tunisia, the results do not conform with what MABP predicted. The implicit conclusion is that an increase in domestic credit causes a continuous loss of net foreign assets in Egypt, Jordan, Morocco, and Algeria. Thus, monetary authorities should formulate an appropriate monetary policy to control the domestic credit creation as a mechanism toward improving the balance of payment (BOP) position. Furthermore, the policymakers should concentrate on other policy instruments to correct the BOP deficit rather than focusing on monetary tools, especially in Tunisia, where the findings showed that BOP was not a monetary phenomenon.